The Distribution of Pubertal Age among Male School Students in Jatinangor District from April to June 2013 - Karthik Yogaswaran; Anggraini Widjajakusuma; Juliati Juliati (Althea Medical Journal, 2016)
Background: Puberty is important and exciting lifetime changes in an individual. Many new changes are experienced during puberty, such as physically, mentally, and emotionally. Currently, young males worldwide have different onset of pubertal age. Many factors may result in this change of pubertal age. The exact pubertal age was still unknown due to less study conducted previously. Therefore, the aim of this study was to identify the distribution of pubertal age among male school students in Jatinangor.Methods: A descriptive study was conducted from April to June 2013. A secondary data were obtained from the Jatinangor Cohort Study, from the Department of Epidemiology and Biostatistics, Faculty of Medicine, Universitas Padjadjaran. The samples were taken via cluster random sampling from 48 schools around Jatinangor. Randomization was conducted and a total of 219 male students were finally obtained from the overall data which had at least single onset of pubertal changes. This presents a response rate of 82.33%.Results: The earliest onset of pubertal age was identified as 9 years old and the oldest onset was 18 years old. The majority onset of pubertal age ranged from 12 to 15 years old with average mean of 13 years. Voice changes were identified as the early sign of puberty among males.Conclusions: Majority of the students undergo puberty at age 13 which is earlier compared to previous studies. Thus, this study indicates decreasing in onset of pubertal age among male school students in Jatinangor. [AMJ.2016;3(1):6–11] DOI: 10.15850/amj.v3n1.698